Effect of the starting and turning performances on the subsequent swimming parameters of elite swimmers - Veiga, S.; Roig, A. (Sports Biomechanics, 2017)
In the present research, we examined the effect of the starting and turning performances on the subsequent swimming parameters by (1) comparing the starting and turning velocities with the swimming parameters on the emersion and mid-pool segments and (2) by relating the individual behaviour of swimmers during the start and turns with subsequent behaviour on each swimming lap. One hundred and twelve 100m performances on the FINA 2013 World Swimming Championships were analysed by an image-processing system (InThePool 2.0®). At the point of the start emersion, the swimming parameters of the 100-m elite swimmers were substantially greater than the mid-pool parameters, except on the breaststroke races. On the other hand, no diminution in the swimming parameters was observed between the turn emersion and the mid-pool swimming, except on the butterfly and backstroke male races. Changes on the surface swimming kinematics were not generally related to the starting or turning parameters, although male swimmers who develop faster starts seem to achieve faster velocities at emersion. Race analysts should be aware of a transfer of momentum when swimmers emerge from underwater with implications on the subsequent swimming kinematics, especially for male swimmers who employ underwater undulatory techniques. ABSTRACT FROM AUTHOR